Modulation of Bacterial Multidrug Resistance Efflux Pumps of the Major Facilitator Superfamily. (5th December 2013) - Kumar, Sanath; Mukherjee, Mun Mun; Varela, Manuel F.
Abstract : Bacterial infections pose a serious public health concern, especially when an infectious disease has a multidrug resistant causative agent. Such multidrug resistant bacteria can compromise the clinical utility of major chemotherapeutic antimicrobial agents. Drug and multidrug resistant bacteria harbor several distinct molecular mechanisms for resistance. Bacterial antimicrobial agent efflux pumps represent a major mechanism of clinical resistance. The major facilitator superfamily (MFS) is one of the largest groups of solute transporters to date and includes a significant number of bacterial drug and multidrug efflux pumps. We review recent work on the modulation of multidrug efflux pumps, paying special attention to those transporters belonging primarily to the MFS.